2020
DOI: 10.1111/febs.15640
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and spatial mechanisms governing STING signalling

Abstract: Detection of microbial nucleic acids via innate immune receptors is critical for establishing host defence against pathogens. The DNA-sensing cGAS-STING pathway has gained increasing attention in the last decade as a key pathway for combating viral and bacterial infections. cGAS-STING activation primarily promotes the secretion of antiviral type I IFNs via the key transcription factor, IRF3. In addition, cGAS-STING signalling also elicits pro-inflammatory cytokines through NF-B activity. Activation of IRF3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 182 publications
(417 reference statements)
2
30
0
Order By: Relevance
“…Proteins and mechanisms involved in movements of cGAS-STING across intracellular compartments are being increasingly elucidated and illustrate the critical role of trafficking for signal regulation [reviewed in ( 64 )]. STIM1 is an ER-resident Ca2 + binding protein implicated in replenishing Ca2 + stores at ER-plasma membrane (ER-PM) contact sites.…”
Section: Cgas-sting Trafficking and The Connection With The Cytoskeletonmentioning
confidence: 99%
“…Proteins and mechanisms involved in movements of cGAS-STING across intracellular compartments are being increasingly elucidated and illustrate the critical role of trafficking for signal regulation [reviewed in ( 64 )]. STIM1 is an ER-resident Ca2 + binding protein implicated in replenishing Ca2 + stores at ER-plasma membrane (ER-PM) contact sites.…”
Section: Cgas-sting Trafficking and The Connection With The Cytoskeletonmentioning
confidence: 99%
“…Recent studies showed that some purinergic ectoenzymes metabolize cyclic dinucleotides, such as 2',3'cyclic GMP-AMP (cGAMP) (21). CD203a/ENPP1 metabolizes cGAMP generating AMP and GMP (22). cGAMP is an activator of the stimulator of interferon genes (STING), which stimulate innate immunity.…”
Section: Inhibition Of Anti-tumor Immunitymentioning
confidence: 99%
“…Links between the cGAS-STING pathway with CD203a/ENPP1 and NAD + have recently emerged whereby the hydrolysis of cGAMP by CD203a/ENPP1 attenuates cGAS-STING signaling and NAD + cleavage (23,24). Indeed, bacterial STING, containing a NADase-TIR domain, recognizes cyclic dinucleotides in a conformation similar to cGAMP in complex with human STING, allowing for b-NAD + hydrolysis (22). NAD + cleavage activity of bacterial TIR domains is conserved in the mammalian SARM1 (sterile alpha and TIR motif containing 1) NAD + -glycohydrolase (23,25).…”
Section: Inhibition Of Anti-tumor Immunitymentioning
confidence: 99%
“…Then, cGAMP acts as a secondary messenger to activate the Stimulator of Interferon Genes (STING), inducing its conformational change and subsequent activation (Ablasser et al, 2013;Wu et al, 2013;Sun et al, 2013). In its activated form, STING interacts with Tank-binding Kinase I (TBK1) and the IKK complex to activate them, which leads to STING phosphorylation by TBK1, then recruitment and activation of IRF3 followed by the release of Nuclear Factor-kappaB (NF-kB), ultimately promoting the production of IFN-I and other inflammatory cytokines (Balka and De Nardo, 2021). During acute immune responses, IFN-I activation is usually beneficial to the host by providing transcriptional changes that allow the orchestration of an efficient response.…”
Section: Sensing Of Nucleic Acids By Cellular Receptors Activates The...mentioning
confidence: 99%